Building Community Resilience via Transformative Adaptation: Creating Alternative Livelihood Opportunities in Belize - Williams, Stephen (2019)
This project will work with five agriculture-based community groups that are established and are implementing sustainable food production systems and nature-based enterprises but need support to strengthen their activities, develop their ideas and strategies, and access the market. A member's farm will be selected to establish a demonstration plot in sustainable food production and members who need support in nature-based enterprise development will be identified. This is a collaborative project between IICA, the Ministry of Agriculture, Beltraide, and the Department of Cooperatives. It is being implemented by PACT (Protected Area Conservation Trust) with funding from the Adaptation Fund.